TECHNOLOGY OF QUICK HOT EXTRUSION OF ROD PRODUCTS WITH END FACE CLADDING - I. V. Kachanov (Nauka i Tehnika, 2008)
The paper proposes a technology for manufacturing, strengthening and restoration of rod stamp tools which is based on a method of quick hot extrusion of rod products with end face cladding.Dependences have been obtained for determination of an optimal upsetting during a cladding process which is necessary for formation of a high-quality welded joint.